Zakres oddziaływania interesariuszy na rozwój przedsiębiorstwa rolnego z sektora bezpośredniej sprzedaży produktów rolnych - Dziedzic, Sylwia (Impact Scope of Stakeholders on the Development of an Agriculture Enterprise in Direct Sales Sector of Agriculture Products, 2008)
The paper presents a detailed analysis of an agriculture enterprise operating within the sector of direct sales. The author uses stakeholders analysis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 66-74